(untitled) (Efficient: Indonesian Journal of Development Economics, 2025)
Economic growth usually shows how much a country has grown. The ASEAN-5 which includes Indonesia, Malaysia, Thailand, Singapore, and the Philippines are important for Southeast Asia’s economy. This study examines the effect of government spending, gross fixed capital formation, and labor on economic growth in the period 2000–2023 using secondary data from the World Bank. This study applies panel data regression through the Fixed Effects Model (FEM). The findings show that government spending, gross fixed capital formation, and labor have a positive and significant impact on economic growth in the ASEAN-5 countries. Thus, the effectiveness of government spending, optimization of fixed capital investment, and utilization of productive labor are important factors in promoting sustainable economic growth in the region.